Policy and Research Trends in Carbon Trading Stock Exchanges for Financial Reporting: A Systematic Review Using Bibliometric Network Analysis - Purwanti, Ari; Misdiyono, Misdiyono; Setiawan, Temy (Universitas Pendidikan Ganesha, 2025)
This study presents a comprehensive bibliometric analysis of carbon trading stock exchanges for financial reporting, focusing on the Indonesian market. A total of 331 documents published between 2015 and 2024 were examined using the Biblioshiny tool within the Bibliometrix framework. The research investigates the evolution of key themes, the geographic distribution of publications, and the contributions of leading authors and journals in this field. The findings reveal that carbon trading research has grown steadily, with a marked increase in publications over the last five years, predominantly in academic journals (88%) compared to conference papers (12%). Notably, the United Kingdom has made significant contributions to this research domain, with Zhang Y emerging as a leading researcher. The most influential journals identified include Energy Policy, Sustainability (Switzerland), and the Journal of Cleaner Production. The study also provides a detailed analysis of research trends, showing the increasing prominence of carbon trading, its correlation with financial reporting, and its global impact. This bibliometric review offers valuable insights for scholars and practitioners seeking to understand the development and future directions of carbon trading in financial markets, as well as the evolving collaborative networks between institutions and countries.